Técnicas para avaliação do desempenho térmico e lumínico associado a sistemas de prateleira de luz em clima quente e úmido - SILVA, Marcelle Vilar da (Universidade Federal do Pará, 2017)
When using a daylight system in a hot and humid climate region, with a elevated number of hours of insolation and high intensity of solar radiation, it is mandatory to evaluated the effects on the thermal performance and environmental luminosity, to identify their potential for use in a controlled and appropriate manner. The aim is to carry out a performance analysis, but more specifically ensure a critic and carefull approach to methodology for assessing the increase of heat, light gains -in hot and humid climate-, through fenestrations with shading protection systems, the comparative studies of efficiency where done to compared systems with and without shading protection through the calculation of solar heat gains using the CSTB method (adapted by Frota e Schiffer), internal illuminance levels where done with computer simulations (RELUX 2006), variation of internal temperatures (ECOTEC v.2) and measurements under real sky condition, with reduced scale models, air temperature measurement, globe temperature and internal and external illuminance, using data loggers, for calculating the daylight coefficient (CLD), infrared thermal imaging to monitor the internal and external surface temperatures. Processing data with auxiliary of regression curves where used to ensure the accuracy of the measurements and identify the quality of the equipment and data refinement. Where verified as results that the systems had very similar performance, but with some relative indicative differences levels for internal illuminance. The shading method analyses shown similar analytical angle generated by the solar protections adopted the prototypes, offering a 40.14% reduction on the thermal load for the north façade. The simulations indicate that the proposed lightshelf could reveal potencial for luminance levels improvements at the center portion of the environment when compared to the tradicional shading device, indicative of potential for future studies. The internal temperature measurements generated very close values between the shelf and the traditional light shading device, what was not enough to demonstrate differential heating. Studies in infrared shown to be efficient to identify surfaces temperatures conditions as thermal energy – heat gains -, drived inside by the boards of the shading device and the lightshelf. For the light shelf the internal illuminance measurements showed significantly increased levels near the window, and at the more inner illuminance measurement point presented an difference of 500lux , this specifically occurred regarding the traditional shading device only 11:00 to 13:30. The DLF – Day Light Factor - indicated that the availability of light in the environment of the center position of the prototype is higher with light shelf than with the traditional shading device and in the more inner illuminance measurement point both indicate mostly similar performances.